Pengaruh Gaya Kepemimpinan dan Kompleksitas Tugas terhadap Hubungan Partisipasi Penyusunan Anggaran dengan Kinerja Aparat Pemerintah Daerah Kabupaten Karanganyar - Noviana Puspitasari (Master Manajemen, 2025)
This research uses a survey method using primary data obtained from questionnaire. The population in this study were Head of Service Level Officials and Heads of Divisions/Fields/Sub-Departments in the Regional Government of Karanganyar Regency. The samples taken were officials at the level of Head of Service and Head of Section/Field/Sub-Department in BAPPEDA, DPPKAD and BKD in accordance with the research permit letter from the KESBANGPOLINMAS Agency. The number of samples in this research was 43 respondents taken using purposive sampling technique. The data analysis technique uses the t test to test the hypothesis. The research results show that: (1) Participation in budget preparation influences the performance of regional government officials and H1 is supported by statistical testing at a significance level of 0.005 (p<0.05). (2) Leadership style influences the relationship between budget preparation participation and apparatus performance and H2 is supported statistically at a significance level of 0.032 (p<0.05). This shows that leadership style acts as a moderating variable which influences the relationship between budget preparation participation and apparatus performance. (3) Task complexity influences the relationship between budget preparation participation and apparatus performance and H3 is not supported statistically at the significance level of 0.136 (p>0.05).